Differences in GPA by Gender and Ethnicity/Race as a Function of First-Generation Status for Community College Students (Global Journal of Human-Social Science, 2017)
In this investigation, the degree to which GPAs might be different between firstgeneration and non-first-generation students by gender and ethnicity/race for community college students was addressed. Utilizing a 25% random sample of responses from the Community College Survey of Student Engagement (CCSSE), student success as a function of their gender and race/ethnicity was analyzed. Student success was statistically significantly different between first-generation and non-first-generation students by gender and by ethnicity/race. In all cases, GPAs were higher for non-first-generation students than for first-generation students. Implications of the results were discussed.
Keywords: first-generation students; community college; gpa; gender; ethnicity/race